2007
DOI: 10.1042/bj20070236
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol is a class IA phosphoinositide 3-kinase inhibitor

Abstract: Resveratrol, a polyphenol found in fruits, possesses chemopreventive and chemotherapeutic properties and has been shown to increase lifespan in yeast and metazoans, including mice. Genetic evidence and in vitro enzymatic measurements indicate that the deacetylase Sir2/SIRT1, an enzyme promoting stress resistance and aging, is the target of resveratrol. Similarly, down-regulation of insulin-like pathways, of which PI3K (phosphoinositide 3-kinase) is a key mediator, promotes longevity and is an attractive strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(61 citation statements)
references
References 51 publications
(74 reference statements)
9
51
1
Order By: Relevance
“…2B). This result is also consistent with a recent finding that RSV suppresses PI3K signaling by binding to the ATP-binding site of PI3K (37,39). However, inhibition of Akt did not completely block the inhibitory effect of RSV on mTOR activity (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…2B). This result is also consistent with a recent finding that RSV suppresses PI3K signaling by binding to the ATP-binding site of PI3K (37,39). However, inhibition of Akt did not completely block the inhibitory effect of RSV on mTOR activity (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…In relation to the interaction between insulin signaling pathway and resveratrol, it was shown that resveratrol did not affect expression levels of IRS-1 and IRS-2 [32], consistent with our previous results in the vasculature of male rats [11]. However, resveratrol reduced IRS-1/2 serine/threonine phosphorylations, which are the feedback inhibitors of insulin signaling pathway, and thus promoted the insulin sensitivity [33].…”
Section: Discussionsupporting
confidence: 78%
“…activation, Akt, mTOR, p38, and Hsp27 are all induced in response to Cmpd1 (Fig. 6), which is indicative of pleiotropic effects, as has been observed for resveratrol and its metabolites (Yu et al, 2001;Fröjdö et al, 2007;Pirola and Fröjdö, 2008;Pervaiz and Holme, 2009;Calamini et al, 2010). To what extent the combination of these changes facilitates the growth inhibitory effects of Cmpd1 is presently unclear.…”
Section: Discussionmentioning
confidence: 95%